The McGraw-Hill handbook - Maimon, Elaine P. (McGraw-Hill Companies,Incorporated, 2009)
As we wrote the first edition of The McGraw-Hill Handbook, our students were in our minds, acting as our chief consultants. We knew that their perspectives on college life were different from those of previous generations of students, and so were their expectations. We understood that they needed a handbook for the twenty-first century, with state-of-the-art resources on writing, researching, and graphic design. They might be using a handbook in an English composition class at 9:00 AM, but at 10:00 AM they might be preparing PowerPoints for a speech course, and at 11:00 AM they might need the handbook to help with a history assignment. More than any other textbook, their handbook was their guide, not just to writing, but also to learning in college.